EVALUATION OF HEPATOPROTECTIVE POTENTIAL OF APOCYNACEAE FAMILY PLANTS IN RAT MODELS OF ALCOHOL, PARACETAMOL, AND RANITIDINE-INDUCED HEPATOTOXICITY - SUBBA RAO CHAMAKURI; ASHISH SUTTEE; PRASENJIT MONDAL; DASARI PRIYANKA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to evaluate the hepatoprotective activity of the methanolic leaf extract of Plumeria pudica (PP) against hepatotoxicity induced by Paracetamol, ethanol, and ranitidine in rat models. Methods: The presence of key bioactive constituents, such as saponins and flavonoids in the methanolic extract of PP leaves was confirmed through gas chromatography-mass spectrometry analysis. Rats were divided into six groups (n=6/group). Hepatotoxicity was induced using Paracetamol, ethanol, and ranitidine. Silymarin served as the standard reference drug. The extract was administered at various doses, and hepatoprotective activity was assessed in comparison with the control group. Results: Treatment with PP extract significantly reduced the levels of aspartate transaminase, alanine transaminase, serum total bilirubin, total protein, triglycerides, and cholesterol when compared to the toxicant-treated group (Group II). Histopathological examination revealed reduced hepatic necrosis and inflammation, supporting the biochemical findings. Conclusion: The methanolic leaf extract of PP demonstrated significant (p<0.05*, p<0.01**, p<0.001***) hepatoprotective effects in rat models of drug- and alcohol-induced liver injury. These effects are attributed to the presence of saponins and flavonoids, which may contribute to membrane stabilization and antioxidant properties.